(untitled) (Shahroud Journal of Medical Sciences, 2021)
Background: Given that the important characteristics of drug abuse are high relapse rate and craving, the use of new therapeutic interventions that help drug dependents can be very important. The present study aimed to investigate the effectiveness of logotherapy intervention program in reducing drug cravings and preventing relapse among males with substance dependence in Ahvaz in 2019. Methods: The research method was quasi-experimental with a pretest-posttest design and a control group. The statistical population included all the males with addiction disorder who were referred to treatment centers in Ahvaz city during 2018. Using convenience sampling, we selected 30 males with addiction disorder willing to participate in the study and randomly divided them into experimental and control groups (n=15 per group). The research instruments included Gorski's Warning Signs of a Relapse and the Craving Questionnaire. The experimental group underwent eight sessions (90-minute sessions per week) of the logotherapy intervention program. Multivariate analysis of covariance (MANCOVA) was used to analyze the data. SPSS version 22.0 was further used to analyze the data. Results: The mean ± SD of the drug craving for experimental and control groups in the post-test phase was 36.46±6.77 and 49.06±12.95, respectively. The results showed that intervention programs were effective in reducing drug craving and relapse in males with drug addiction (Pvalue= 0.001). Conclusions: Training logotherapy was shown effective in reducing drug cravings and preventing relapse in males with substance dependence, and thus it can be used in drug rehabilitation centers to prevent relapse in clients. Keywords: Logotherapy, Drug craving, Preventing relapse, Drug abuse, Health.